GIP and GLP-1 Potentiate Sulfonylurea-Induced Insulin Secretion in Hepatocyte Nuclear Factor 1α Mutation Carriers - Christensen, Alexander S. (Diabetes, 2020)
Sulfonylureas (SUs) provide an efficacious first-line treatment in patients with hepatocyte nuclear factor 1α (HNF1A) diabetes, but SUs have limitations due to risk of hypoglycemia. Treatment based on the incretin hormones glucose-dependent insulinotropic peptide (GIP) and glucagon-like peptide 1 (GLP-1) is characterized by their glucose-dependent insulinotropic actions without risk of hypoglycemia. The effect of SUs together with GIP or GLP-1, respectively, on insulin and glucagon secretion in patients with HNF1A diabetes is currently unknown. To investigate this, 10 HNF1A mutation carriers and 10 control subjects without diabetes were recruited for a double-blinded, placebo-controlled, crossover study including 6 experimental days in a randomized order involving 2-h euglycemic-hyperglycemic clamps with coadministration of: 1) SU (glimepiride 1 mg) or placebo, combined with 2) infusions of GIP (1.5 pmol/kg/min), GLP-1 (0.5 pmol/kg/min), or saline (NaCl). In HNF1A mutation carriers, we observed: 1) hypoinsulinemia, 2) insulinotropic effects of both GIP and GLP-1, 3) additive to supra-additive effects on insulin secretion when combining SU+GIP and SU+GLP-1, respectively, and 4) increased fasting and arginine-induced glucagon levels compared with control subjects without diabetes. Our study suggests that a combination of SU and incretin-based treatment may be efficacious in patients with HNF1A diabetes via potentiation of glucose-stimulated insulin secretion.